2021
DOI: 10.1016/j.worlddev.2021.105397
|View full text |Cite
|
Sign up to set email alerts
|

Fractal urbanism: City size and residential segregation in India

Abstract: We present the first ever large-scale snapshot of urban residential segregation in India at the neighborhood-scale. Our analysis from 147 largest cities in contemporary India shows how caste-based residential segregation is independent of city size (our sample includes all cities in India with at least 0.3 million residents in 2011). The extent of segregation in the largest metropolitan centers with over ten million residents closely tracks cities that are nearly two orders-of-magnitude smaller. We also show h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…The determination of building prices was also limited to structural fac were part of the determinants of property costs [11,12]. This confirmed that th factor of the building was related to the number of bedrooms and bathrooms area, terrace, property age, and the size of the plot [13]. To simplify the calcu cost of development in an area was then determined based on the administr at the sub-district level.…”
Section: Resultsmentioning
confidence: 87%
“…The determination of building prices was also limited to structural fac were part of the determinants of property costs [11,12]. This confirmed that th factor of the building was related to the number of bedrooms and bathrooms area, terrace, property age, and the size of the plot [13]. To simplify the calcu cost of development in an area was then determined based on the administr at the sub-district level.…”
Section: Resultsmentioning
confidence: 87%
“…Yuval‐Davis (2015) delineates the three central aspects of a situated intersectional analysis—translocality, transcalarity and transtemporality—pointing to the importance of considering the situated gazes of people in relation to their geographical, social and temporal location. To illustrate translocality, a woman vendor's livelihood depends on things such as her living conditions and the length of her commute to the market, which in turn would be determined by her caste and class location—Mumbai, like most Indian cities, is highly stratified by caste, even at the neighbourhood level (Bharathi et al., 2021). Transcalarity comes in when we look at the woman vendor as being part of a broader supply chain that is influenced by various flows of power at different scales—home, neighbourhood, regional, national and global.…”
Section: Towards An Intersectional Feminist Geographymentioning
confidence: 99%
“…This has led to a long and entrenched history of residential segregation in the United States. In another example, recent research on urbanization in India indicates that caste‐based segregation is rife (Bharathi et al., 2021), suggesting that the implications of historical policy decisions must be considered in current urban system design if the aim is to also erode the social construct of caste ascription.…”
Section: Social Equity and Justicementioning
confidence: 99%